Human papillomavirus vaccine initiation in Asian Indians and Asian subpopulations: a case for examining disaggregated data in public health research. (December 2017) - Budhwani, H.; De, P.
Abstract: Objectives: Vaccine disparities research often focuses on differences between the five main racial and ethnic classifications, ignoring heterogeneity of subpopulations. Considering this knowledge gap, we examined human papillomavirus (HPV) vaccine initiation in Asian Indians and Asian subpopulations. Study design: National Health Interview Survey data (2008–2013), collected by the National Center for Health Statistics, were analyzed. Methods: Multiple logistic regression analysis was conducted on adults aged 18–26 years ( n  = 20, 040). Results: Asian Indians had high income, education, and health insurance coverage, all positive predictors of preventative health engagement and vaccine uptake. However, we find that Asian Indians had comparatively lower rates of HPV vaccine initiation (odds ratio = 0.41; 95% confidence interval = 0.207–0.832), and foreign-born Asian Indians had the lowest rate HPV vaccination of all subpopulations (2.3%). Conclusions: Findings substantiate the need for research on disaggregated data rather than evaluating vaccination behaviors solely across standard racial and ethnic categories. We identified two populations that were initiating HPV vaccine at abysmal levels: foreign-born persons and Asian Indians. Development of culturally appropriate messaging has the potential to improve these initiation rates and improve population health. Highlights: Provides evidence to support the need for studies that examine disaggregated data. Addresses nativity as an associate of human papillomavirus (HPV) vaccination in Asian subgroups. Offers an innovative analysis of early-adopter adult HPV vaccine initiation. Asian Indians had the lowest odds of HPV vaccine compared to other Asian subgroups. Education, sex, nativity, and health insurance were associated with vaccination.